Dukungan Keluarga, Kesiapan Persalinan, dan Pengetahuan tentang Covid-19 sebagai Determinan Kecemasan Ibu Hamil Selama Pandemi - Apri Nur Wulandari; Eny Septi Wulandari Dwi Prihatin (Malahayati Nursing Journal, 2025)
ABSTRACT The COVID-19 pandemic has had a significant impact on mental health, especially in vulnerable populations like pregnant women. The anxiety experienced by pregnant women during the pandemic is a particular concern because it can have negative effects on both the mother and the fetus, and can also lead to long-term consequences that may affect a child's development. This study aims to identify the factors associated with anxiety and the dominant factor contributing to anxiety in pregnant women during the COVID-19 pandemic. This was an analytical study with a cross-sectional design. The research was conducted in three Community Health Centers in the Special Region of Yogyakarta, an area with a high number of COVID-19 cases. A convenience sampling method was used to collect samples from April to May 2022. The total sample size for this study was 118 pregnant women. The results of statistical tests using the Kruskal-Wallis and Chi-Square correlations showed a significant relationship between knowledge about COVID-19, family support, and childbirth readiness with anxiety in pregnant women during the COVID-19 pandemic (p-value 0.005). These factors collectively influenced 59% of the anxiety in pregnant women during the COVID-19 pandemic (R2 adjusted = 0.587; p = 0.002). The dominant factor affecting anxiety in pregnant women was family support (β = 0.305; p = 0.001). Family support, childbirth readiness, and knowledge about COVID-19 are factors associated with anxiety in pregnant women during the COVID-19 pandemic. Family support is the dominant factor in the occurrence of anxiety in pregnant women. The findings suggest that providing pregnant women with social and emotional support through their families is vital to mitigating the psychological effects on both the mother and the fetus. Additionally, implementing effective educational strategies is necessary to improve pregnant women's understanding of global health crises. Keywords: Anxiety In Pregnant Women, Childbirth Readiness, COVID-19 Pandemic, Family Support  ABSTRAK Pandemi COVID-19 telah memberikan dampak yang besar terhadap kesehatan mental, terutama pada kelompok rentan seperti ibu hamil. Kecemasan ibu hamil pada masa pandemi menjadi perhatian khusus karena dapat memberikan dampak negatif pada ibu maupun janin, dan juga bisa berdampak jangka panjang yang nantinya bisa mempengaruhi perkembangan anak.  Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan kecemasan dan faktor dominan terjadinya kecemasan ibu hamil pada masa pandemi COVID-19. Penelitian ini merupakan penelitian analitik dengan desain cros sectional. Penelitian dilakukan di 3 Puskesmas yang berada di wilayah Daerah Istimewa Yogyakarta, dengan jumlah kasus COVID tinggi. Cara pengambilan sampel menggunakan convenience sampling yang didapat dari bulan April-Mei 2022. Jumlah sampel dalam penelitian ini adalah 118 ibu hamil. Hasil uji statistik dengan menggunakan korelasi Kruskal Wallis dan Chi Square menunjukkan bahwa terdapat hubungan yang bermakna antara pengetahuan tentang Covid-19, dukungan keluarga dan kesiapan persalinan dengan kecemasan ibu hamil pada masa pandemic Covid-19 (p-value 0,005). Faktor-faktor tersebut secara bersama-sama dapat mempengaruhi kecemasan pada ibu hamil di masa pandemi Covid-19 sebanyak 59 % (adjusted R2 = 0,587; p = 0,002). Faktor dominan yang mempengaruhi kecemasan ibu hamil adalah dukungan keluarga (β = 0,305; p = 0,001). Dukungan keluarga, kesiapan persalinan dan pengetahuan tentang Covid-19 adalah faktor-faktor  yang berhubungan dengan kecemasan ibu hamil pada masa pandemi COVID-19. Dukungan keluarga sebagai faktor dominan terjadinya terjadinya kecemasan ibu hamil. Pemenuhan dukungan sosial dan emosional ibu hamil melalui peran keluarga merupakan hal yang penting guna meminimalkan dampak psikologis pada ibu dan janin. Strategi edukasi yang efektif perlu dilakukan untuk meningkatkan pemahaman ibu tentang masalah kesehatan global yang sedang terjadi. Kata Kunci: Dukungan Keluarga, Kecemasan Ibu Hamil, Kesiapan Persalinan, Pandemi COVID-19